ANALISIS FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL STATEMENT - Wiranti, Sri; Marhamah, Marhamah; Mardawati, Verani Ari (JURNAL STIE SEMARANG, 2022)
Abstract. Fraudulent financial statements often occur in companies, especially in government-owned companies. This is because there are differences in interests between management and the government, where the government wants the company's conditions to be fine but the management does not achieve the expectations that the government wants. This study aims to empirically examine the effect of pressure, opportunity, rationalization, capability and arrogance on fraudulent financial statements in state-owned companies listed on the IDX. The population in this study were 20 state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The sample in this study used the purposive sampling method in order to obtain a sample of 11 issuers. The variables in this study are pressure, opportunity, rationalization, capability, arrogance and fraudulent financial statements. The data collection method used is data polling or a combination of time series and cross section data. The analytical method used in this research is descriptive analysis and logistic regression analysis. Based on the results of data analysis, it is concluded that the pressure variable has no significant effect on the fraudulent financial statement, the opportunity variable has no significant effect on the fraudulent financial statement, the rationalization variable has no significant effect on the fraudulent financial statement, and the capability variable. significant effect on fraudulent financial statements, arrogance variable has no significant effect on fraudulent financial statements. Suggestions that can be given to investors and potential investors, to be more careful and thorough in investing their assets in companies that are not detected as committing fraud. For company management (issuers), to carry out their obligations and duties in accordance with existing rules and based on common interests, not personal interests. Abstraksi. Kecurangan laporan keuangan (Fraudulent Financial Statement) sering terjadi pada perusahaan terutama pada perusahaan-perushaan milik pemerintah. Hal ini dikarenakan adanya perbedaan kepentingan antara manajemen dengan pemerintah, dimana pemerintah menginginkan kondisi perusahaan yang baik-baik saja namun pihak manajemen tidak mencapai harapan yang diinginkan pemerintah. Penelitian ini bertujuan untuk menguji secara empiris pengaruh tekanan, peluang, rasionalisasi, kemampuan dan arogansi terhadap fraudulent financial statement pada perusahaan BUMN yang terdaftar di BEI. Populasi dalam penelitian ini adalah 20 perusahaan BUMN yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2014-2018. Sampel dalam penelitian ini menggunakan menggunakan metode Purposive Sampling sehingga diperoleh sampel sebanyak 11 emiten. Variabel dalam penelitian ini adalah tekanan, peluang, rasionalisasi, kemampuan dan arogansi dan fraudulent financial statement. Metode pengumpulan data yang digunakan adalah poling data atau gabungan antara time series dan data cross section. Metode analisis yang digunakan dalam penelitian ini adalah analisis deskriptif dan analisis regresi logistik. Berdasarkan hasil analisis data disimpulkan bahwa variabel tekanan tidak berpengaruh signifikan terhadap fraudulent financial statement, Variabel peluang tidak berpengaruh signifikan terhadap fraudulent financial statement, Variabel rasionalisasi tidak berpengaruh signifikan terhadap Fraudulent Financial Statement, Variabel kemampuan berpengaruh signifikan terhadap fraudulent financial statement, Variabel arogansi tidak berpengaruh signifikan terhadap fraudulent financial statement. Saran yang dapat berikan kepada investor dan calon investor, agar lebih berhati-hati dan teliti didalam menginvestasikan asetnya pada perusahaan yang tidak terdeteksi melakukan kecurangan. Bagi manajemen perusahaan (emiten), agar menjalankan kewajiban dan tugas-tugasnya sesuai dengan aturan yang ada dan berdasarkan kepentingan bersama bukan atas kepentingan pribadi.